Development of Vocabulary Learning Videos to Improve Students' Motivation and Understanding of Arabic Vocabulary - Ida Latifatul Umroh; Ellina Dwi Faning Zun; Nurotun Mustaqimah (LISANIA: Journal of Arabic Education and Literature, 2024)
This research is motivated by the low motivation to learn Arabic and understand vocabulary at the elementary level. This study aims to produce a product in the form of vocabulary learning videos and describe its feasibility in increasing learning motivation and understanding of Arabic vocabulary. The type of research is research and development. The research data from the results of the validation of material and media experts, limited field tests assessing the language learning motivation, and effectiveness of Arabic vocabulary learning videos. The data collection technique uses observation and questionnaires. The results of the research are: (1) the product was developed in the form of learning video media to increase learning motivation and understanding of Arabic vocabulary at the beginner level. This product contains images that symbolize the meaning of words. This product presents one learning theme, natural scenery, consisting of nine vocabularies. This product also contains exercises to help students understand Arabic vocabulary. (2) The product feasibility from both material and media experts is good. The results of limited field tests of the product use are excellent, while the pilot test for student motivation is high. Therefore, this medium is valuable and should be used in learning.